Dampak Pelatihan Teknik Role Playing terhadap Keterampilan Komunikasi Interpersonal Siswa - Wariyanti Wariyanti; Arifin Nur Budiono; Sri Prawita (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2018)
Communication is the daily activities most carried out by humans os social being. The researchers conducted observation in class VII hare low interpersonal communication skills. This study aines to determine the impact of role playing training techtgues to improve interpersonal communication skills of student in grade VII second semester MTs As Shiddiqy Pakis-Panti of academic year 2017/2018. This research used is pre experiment the procedure used  is one group pretest deseign, pretest result subject recerved a score of 70, 68, 73, 69, 71, 64, 72, 69 which included the category of low interpersonal communication skills. Posttest result after receiving treatment score of 90, 84, 91, 85, 93, 87, 91, 87 than the value of count = -1,260 is greather than z table it proves that the training role playing techniques affect interpersonal communication skills.  Keywords : Role playing, Interpersonal Communication.